2017
DOI: 10.5812/ijp.11844
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Peripheral Neuropathy in a Subpopulation of Mexican Pediatric Patients with Acute Lymphoblastic Leukemia

Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is frequent in children with acute lymphoblastic leukemia (ALL). Neurological manifestations can be grouped into one of the three functional divisions of the peripheral nervous system (PNS): sensory, motor and autonomic. One of the chemotherapeutic agents used in ALL is vincristine which has been associated with neuropathy in these children. This type of neuropathy can be transient but also leave permanent sequels that decrease patient's quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…According to the morphology and risk classification, the results in this study were similar to the previous studies 13,14 . B-cell type immunophenotype and high-risk classification were 80% and 50%, respectively in study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the morphology and risk classification, the results in this study were similar to the previous studies 13,14 . B-cell type immunophenotype and high-risk classification were 80% and 50%, respectively in study.…”
Section: Discussionsupporting
confidence: 90%
“…The previous study in Indian children showed 74 percent of B-cell type 13 . Another study form Mexico reported 93.8% of B-cell type and 59.4% of high-risk classification 14 . In regards to initial blood count at diagnosis of neuropathic patients, the result of this study is similar to the India study, in that the mean hemoglobin was 7.5 g/dl, the median white blood cell count was 6,200 per mm 3 and the median platelet count was 5,600 per mm 3 13 .…”
Section: Discussionmentioning
confidence: 92%